2022
DOI: 10.1021/acs.jpcc.2c06145
|View full text |Cite
|
Sign up to set email alerts
|

Large Room Temperature Bulk DNP of 13C via P1 Centers in Diamond

Abstract: We use microwave-induced dynamic nuclear polarization (DNP) of the substitutional nitrogen defects (P1 centers) in diamond to hyperpolarize bulk 13 C nuclei in both single crystal and powder samples at room temperature at 3.34 T. The large (>100-fold) enhancements demonstrated correspond to a greater than 10 000-fold improvement in terms of signal averaging of the 1% abundant 13 C spins. The DNP was performed using low-power solid state sources under static (nonspi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 76 publications
(146 reference statements)
1
17
0
Order By: Relevance
“…In order to understand what mechanisms are involved, we need to decompose the DNP frequency profile into different mechanisms. Based on the prior success of decomposing the DNP frequency profile at 3.34 T into SE, CE, tCE, and apparent Overhauser effect (OE) DNP mechanisms, we apply the same analysis to the DNP frequency profile acquired at 7 T Figure a,b displays the DNP spectrum at 3.34 and 7 T, respectively, measured at room temperature (in black) and the resulting fit (in green).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to understand what mechanisms are involved, we need to decompose the DNP frequency profile into different mechanisms. Based on the prior success of decomposing the DNP frequency profile at 3.34 T into SE, CE, tCE, and apparent Overhauser effect (OE) DNP mechanisms, we apply the same analysis to the DNP frequency profile acquired at 7 T Figure a,b displays the DNP spectrum at 3.34 and 7 T, respectively, measured at room temperature (in black) and the resulting fit (in green).…”
Section: Resultsmentioning
confidence: 99%
“…DNP is a widely used technique to enhance the intensity of the nuclear magnetic resonance (NMR) signal, but our interest in DNP stems from its sensitivity to the nature of interacting spins. 26,45 A recent DNP study of type-Ib diamond samples by Shimon discussed that the observed truncated cross effect 45 can be explained by the existence of coupled P1 spins in the sample in addition to the isolated P1 center, 26 but the fundamental properties of the coupling, whether they are driven by dipolar or exchange coupling, whether there is crosstalk between the different P1 populations, the population of clustered P1 centers, and the mechanistic origin of the proposed Overhauser DNP effect remained unknown. 46,47 In this study, we uncover the coexistence of clustered and isolated P1 centers in type-Ib diamonds using a combination of multifrequency DNP, pulsed high-frequency EPR, and ELDOR techniques.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations